The Effect of Financial Performance on Firm Value with Financial Distress as an Intervening Variable - Muhtar Sapiri; Fyrdha Faradyba Hamzah; Aditya Halim Perdana Kusuma Putra; Amnah Hadi (Universitas Dharma Wacana, 2022)
This study analyzes the relationship between financial performance variables, financial distress, and firm value. The object of this research is property companies listed on the Indonesia Stock Exchange. The choice of research location is based on the consideration that company value needs to be increased by streamlining financial performance, company value and financial distress. Meanwhile, the time required by the author in this study was two months, from June 2021 to August 2021. In this study, the population is 40 property companies listed on the Indonesia Stock Exchange in 2015-2019. The data analysis method used in this study is to use multiple linear regression analysis to analyze data and path analysis to determine the effect of intervening variables. Path analysis is an extension of multiple linear regression analysis which is useful for estimating the causal relationship between variables that have been previously determined based on theory using SPSS. The results of the analysis state that simultaneously and partially financial performance variables and financial distress have a significant direct effect on the value of property companies listed on the IDX. The direct effect of the financial performance variable on firm value is greater than that on firm value through financial distress as an intervening variable, and the t-count value of the sobel test < from the t-table for each variable, so financial distress is not proven as an intervening variable. Indirectly, the financial performance variable has no significant effect on the value of manufacturing companies listed on the IDX through financial distress as an intervening variable